Pengaruh Profitabilitas dan Keputusan Investasi terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Mediasi pada Perusahaan Subsektor Makanan dan Minuman di Bei Periode 2020–2024 - Rizma Novianti Khaliza; Laila Wardani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
This study aims to examine and analyze the effect of profitability and investment decisions on firm value with dividend policy as a mediating variable in food and beverage subsector companies listed on the Bursa Efek Indonesia during 2020–2024. The type of research used in this study is associative research with a quantitative approach. The data collection method used in this research is secondary data obtained from the companies’ financial statements. The population in this study consisted of 83 companies. The sampling technique used was purposive sampling, resulting in 16 companies as research samples with a total of 80 observation data. Data analysis in this study was conducted using IBM SPSS Statistics 26 and the Sobel test. The results of this study indicate that profitability has a negative and significant effect on dividend policy, investment decisions have a negative and significant effect on dividend policy, profitability has a positive and significant effect on firm value, investment decisions have a positive but not significant effect on firm value, and dividend policy has a positive and significant effect on firm value. Meanwhile, dividend policy as a mediating variable is not able to mediate the relationship between profitability and investment decisions on firm value in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period.